Burnout and labour aspects in the nursing teams at two medium-sized hospitals Burnout y aspectos laborales del personal de enfermería de dos hospitales de medio portea Burnout e os aspectos laborais na equipe de enfermagem de dois hospitais de médio porte - Flávia Maria de França; Rogério Ferrari; Diana Carla Ferrari; Elioenai Dornelles Alves (Universidade de São Paulo, 2012)
PURPOSE: The aim of this study is to identify the occurrence of Burnout Syndrome (BS) and assess its relationship with different labour-related aspects, among nursing professionals at two medium-sizes hospitals in the city of Cáceres. METHOD: This is a transversal and descriptive study, with a sample totalling 141 subjects. As an instrument of research, we used a questionnaire for the limitation of labour-related aspects, with the addition of the Maslach Burnout Inventory (MBI). RESULTS: Out of the 141 professional people considered, 13 had BS, according to the MBI. In relation to the different labour aspects, the professional people most affected were those with: work regime based on pay by the day, a working week of 30 hours, regularly hired, with double employment, lower graduation period, less time spent at the unit, and active in the administrative segment. CONCLUSIONS: Hence, there was the demonstration of the presence of BS within the sample, showing the need for the proposal of organisational changes within the working environment so as to reduce these factors and their interference on the health of the worker. OBJETIVO: Identificar la incidencia de síndrome de Burnout (BS) y evaluar su relación con los aspectos laborales, personal de enfermería de dos hospitales de medio portea de Cáceres. MÉTODO: Se trata de un estudio descriptivo, de corte transversal de la muestra de 141 sujetos. Como instrumento de investigación se utilizó un cuestionario para el delineamiento de los aspectos laborales, aumentando del Maslach Burnout Inventory (MBI). RESULTADOS: De los 141 profesionales, 13 presentaron SB según MBI. Con relación con los aspectos laborales los profesionales más acometidos son aquéllos con: régimen de trabajo diarista, 30 horas semanales de servicio, contratado, doble empleo, menor tiempo formación, poco tiempo en la unidad y actuación en el sector administrativo. CONCLUSIONES:Luego, se demostró la presencia de SB en la muestra, revelando necesidad de proponerse cambios organizacionales en el ambiente de trabajo a fin de apocar estos factores interfieren en la salud del trabajador. OBJETIVO: identificar a incidência da Síndrome de Burnout (SB) e avaliar sua relação com os aspectos laborais, em profissionais de enfermagem de dois hospitais de médio porte de Cáceres, MT. MÉTODO: trata-se de estudo descritivo, transversal, com amostra de 141 sujeitos. Como instrumento de pesquisa utilizou-se um questionário para o delineamento dos aspectos laborais, acrescido do Maslach Burnout Inventory (MBI). RESULTADOS: dos 141 profissionais, 13 apresentaram SB, segundo o MBI. Em relação aos aspectos laborais, os profissionais mais acometidos foram aqueles com regime de trabalho diarista, 30 horas semanais de serviço, contratado, duplo emprego, menor tempo de formação, pouco tempo na unidade e atuantes no setor administrativo. CONCLUSÕES: logo, demonstrou-se a presença da SB na amostra, revelando necessidade de se propor mudanças organizacionais no ambiente de trabalho, a fim de diminuir a interferência desses fatores na saúde do trabalhador.